Capsaicin-responsive corneal afferents do not contain TRPV1 at their central terminals in trigeminal nucleus caudalis in rats - Hegarty, Deborah M. (J Chem Neuroanat, 2014)
We examined the substrates for ocular nociception in adult male Sprague-Dawley rats. Capsaicin application to the ocular surface in awake rats evoked nocifensive responses and suppressed spontaneous grooming responses. Thus, peripheral capsaicin was able to activate the central pathways encoding ocular nociception. Our capsaicin stimulus evoked c-Fos expression in a select population of neurons within rostral trigeminal nucleus caudalis in anesthetized rats. These activated neurons also received direct contacts from corneal afferent fibers traced with cholera toxin B from the corneal surface. However, the central terminals of the corneal afferents that contacted capsaicin-activated trigeminal neurons did not contain TRPV1. To determine if TRPV1 expression had been altered by capsaicin stimulation, we examined TRPV1 content of corneal afferents in animals that did not receive capsaicin stimulation. These studies confirmed that while TRPV1 was present in 30% of CTb-labeled corneal afferent neurons within the trigeminal ganglion, TRPV1 was only detected in 2% of the central terminals of these corneal afferents within the trigeminal nucleus caudalis. Other TRP channels were also present in low proportions of central corneal afferent terminals in unstimulated animals (TRPM8, 2%; TRPA1, 10%). These findings indicate that a pathway from the cornea to rostral trigeminal nucleus caudalis is involved in corneal nociceptive transmission, but that central TRP channel expression is unrelated to the type of stimulus transduced by the peripheral nociceptive endings.